Study of Public Legal Awareness Regarding the Phenomenon of Infidelity (Case Study of Sawahan District, Nganjuk Regency) - Dewi Irawati; Moh Asror Yusuf; Ilham Tohari (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The phenomenon of infidelity in the background is due to a shift in social values, where once disgraceful behavior is now characterized by family breakdown and psychological disorder. Infidelity is clearly contrary to the purposes of marriage, banned by Islamic law, tribal law, and positive law, but lack of compliance and law enforcement causes a weakening of public consciousness in various walks of life. The study aims to explore public legal awareness, identifying the practice of infidelity in shaping public legal awareness of the effects of infidelity in the incom-lined district district. The study is an empirical legal study with a naturalistic and interpretive qualitative approach (verstehen) in a sociological and legal perspective, which is aimed at understanding legal awareness and behavior of society through a descriptive data of field observations, social interaction, and interpretation of the meaning of action without prejudice. The study learned that public legal awareness of indiscretion on the part of infidelity was low because it was better understood as a moral and social matter than as breaking the law, and it tended to be adopted as a family. It is influenced by economic, psychological, communication, social media, and a lack of legal understanding and has a serious impact on individuals, families, and social beliefs. Therefore, strengthening the integration of social and legal norms of Islamic law is necessary to increase awareness of the law and preserve the moral order of society.